"A drane amonges bees" : a gendered analysis of the Paston family and social identity : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, New Zealand - Crawford, Michaela (Massey University, 2021)
This research analyses the Paston men and women through a gendered lens in order to understand how they expressed themselves individually and in the context of their wider social environment. It does this through the analysis of two major gentry life events, marriage and the writing of a will. Marriage was a source of power and control for both men and women in the Paston family. It served as a means to exert authority over others by arranging marriages and it was a way for them to advance themselves both socially and financially within the gentry. This level of authority and control over one’s life depended on factors such as age and status. Like marriage, wills were another avenue through which the Pastons were able to express individuality, control and authority in a system of patriarchy that, in theory, favoured and benefitted first-born sons.
Keywords: 430309 Gender history